Penentuan Jumlah Mahar Dalam Perkawinan Antar Suku - Siagian, Nurainun (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The fundamental problem in this research is the determination of the amount of dowry in intertribal marriages in Hapesong Baru Village, Batang Toru District, South Tapanuli Regency.This problem is motivated by the determination of the amount of dowry in Batak customs if a man wants to marry woman from the Batak Tribe the amount of dowry given is quite high and the average amount is Rp. 30,000,000-Rp. 40,0000,000 (Thirty million rupiah-Fourty million rupiah), in contrast to the Javanese custom in terms of the tradition of determining the amount of dowry to be given by the prospective groom to the prospective bride, it is not too high and the average amount is Rp. 10,000,00-Rp. 20,000,000 (Ten million rupiah-Twenty million rupiah).The research methodology used is qualitative field research, namely research conducted by collecting primary and secondary data on the phenomenon that is happening directly. And this research which becomes the primary data is data obtained directly from the research subject, the primary data of the researcher is the people of Hapesong Baru Village, Batang Toru District, South Tapanuli Regency who are married. Primary legal materials are the Al-Qur’an and Hadist, Book translation dictionary. Furthermore, data collections techniques were carried out by interview,observation, and documentation. The result of this study are, firstly, determining the amount of dowry in intertribal marriages due to different customs in the marriage procedures of the two tribes, namely the marriage customs of the Batak and Javanese marriage customs. The people who get married are the Batak and Javanese. And other things, namely factors, work, educations, and social status.